SHOWER UNTUK PENURUNAN KADAR BESI (Fe) AIR TANAH - Anif Nur Fauziah Arin; Sri Poerwati; Karno (Gema Lingkungan Kesehatan, 2023)
Ground water that is consumed as drinking water is water which has passed processing system or water which has not passed any process that meets the healthstandard/requirements and can be consumed/drunk directly. Drinking water that fulfills the requirements according to the minister of health no 492 of 2010 has the maximum limit of iron (Fe) content which is 0.3 mg/l. The iron (Fe) content of ground water for drinking water in this research location exceeds the established quality standards, which yields 1,20 mg/.The objective of this research is to measure the iron content (Fe) before and after the treatment with the shower by using several variations of height 30 cm, 50 cm, 160 cm.Sampling method applied in this research was the grab sample with 9 times of replication and analyzed by using the Friedman statistic test. And the laboratory tests were carried out by using spectrophotometry.The results of laboratory examinations of iron (Fe) levels in ground water for drinking water after treatment using a shower with a height variation of 30 cm has reduced the iron content.in groundwater by 30.45%, height variation of 50 cm has reduced the iron (Fe)content in groundwater for drinking water which was 50.45%, and a height variation of 160 cm has effectively reduced iron (Fe) level by 80.75% which was the most effective height in reducing iron (Fe) levels. The results obtained have met the quality standards set by Minister of Health No. 492 In 2010. The results of the Friedman Statistical Test showed that there were differences in the decrease in iron (Fe) levels with the use of a circularshower with variations in height of 30 cm, 50 cm and 160 cm, so the hypothesis wasaccepted. In this research, the most effective height can be found by increasing the height of the shower and adding a longer contact time.